A tale of two GRB-SNe at a common redshift of z = 0.54 - Cano, Z.; Bersier, D.; Guidorzi, C.; Margutti, R.; Svensson, K.; Kobayashi, A.; Melandri, A.; Wiersema, K.; Pozanenko, A.; van der Horst, A.; Pooley, G.; Fernandez-Soto, A.; et al. (Oxford University Press, 2011)
We present ground-based and Hubble Space Telescope optical observations of the opticaltransients (OTs) of long-duration Gamma Ray Bursts (GRBs) 060729 and 090618, both at aredshift of z=0.54. For GRB 060729, bumps are seen in the optical light curves (LCs), and thelate-time broad-band spectral energy distributions (SEDs) of the OT resemble those of localType Ic supernovae (SNe). For GRB 090618, the dense sampling of our optical observationshas allowed us to detect well-defined bumps in the optical LCs, as well as a change in colour,that are indicative of light coming from a core-collapse SN. The accompanying SNe for bothevents are individually compared with SN1998bw, a known GRB supernova, and SN1994I, atypical Type Ic supernova without a known GRB counterpart, and in both cases the brightnessand temporal evolution more closely resemble SN1998bw. We also exploit our extensiveoptical and radio data for GRB 090618, as well as the publicly available Swift-XRT data, anddiscuss the properties of the afterglow at early times. In the context of a simple jet-like model,the afterglow of GRB 090618 is best explained by the presence of a jet-break at t - to > 0.5 d.We then compare the rest-frame, peak V-band absolute magnitudes of all of the GRB andX-Ray Flash (XRF)-associated SNe with a large sample of local Type Ibc SNe, concludingthat, when host extinction is considered, the peak magnitudes of the GRB/XRF-SNe cannotbe distinguished from the peak magnitudes of non-GRB/XRF SNe.